Application of Transmedia Storytelling in Spanish Universities:Collaborative Learning, Multi platform and Multi format - Ossorio Vega, Miguel Ángel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
Transmedia Storytelling has demonstrated being useful in production and broadcasting of entertainment and cultural messages, but it is also useful in journalism. So, this article want to analise the possibility of using the rules of transmedia storytelling in the educational world, specialy in universities. Nowadays there are some platforms of collaborative learning, that are used as a complement of the traditional lectures. By platforms and multimedia formats, people can study or enroll to courses, and is not needed to make part of a university, because there is not any geographical or temporal limit. In this article, it is analysed the Spanish case: how the universities, either public or private ones, are enlarging their lectures with contents on the Net, and how these universities are also opening their platforms to other people in order to offer free courses, everything in a collaborative landscape in which the roles of the teacher and the student are sometimes interchangeables.